Mitotane: new facts for an old drug. (October 2019) - Calabrese, A.; Puglisi, S.; Basile, V.; Perotti, P.; Terzolo, M.
Abstract: Adrenocortical carcinoma (ACC) is an aggressive cancer with poor long-term survival. Apart from radical surgery, there is a reduced range of therapeutic possibilities, and mitotane remains the cornerstone of the treatment in the adjuvant and palliative setting. Although many decades after its introduction in clinical practice, there are still many uncertainties surrounding the applied use and the actual benefit of this old drug. Recent adrenocortical carcinoma guidelines suggest adjuvant mitotane for patients at high risk of recurrence and chemotherapy plus mitotane for metastatic disease; moreover, the use of mitotane monotherapy has been proposed in a subset of patients. When using mitotane, physicians have to consider and manage its potential toxicity and endocrine effects that need a complex supporting therapy.